2022
DOI: 10.1037/pspi0000389
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural variation in cooperation: A meta-analysis.

Abstract: Impersonal cooperation among strangers enables societies to create valuable public goods, such as infrastructure, public services, and democracy. Several factors have been proposed to explain variation in impersonal cooperation across societies, referring to institutions (e.g., rule of law), religion (e.g., belief in God as a third-party punisher), cultural beliefs (e.g., trust) and values (e.g., collectivism), and ecology (e.g., relational mobility). We tested 17 preregistered hypotheses in a meta-analysis of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 194 publications
(369 reference statements)
2
11
0
Order By: Relevance
“…However, none of these seven indicators was significantly correlated to mean differences in cooperation across studies ( p-values ≥ 0.292). These findings are consistent with recent meta-analytic work showing no evidence for cross-cultural variation in cooperation more broadly [53]. It is worth mentioning, however, that despite our effort to obtain more studies (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…However, none of these seven indicators was significantly correlated to mean differences in cooperation across studies ( p-values ≥ 0.292). These findings are consistent with recent meta-analytic work showing no evidence for cross-cultural variation in cooperation more broadly [53]. It is worth mentioning, however, that despite our effort to obtain more studies (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…A second limitation is that behavior and outcomes within experimental social dilemmas do not allow us to infer which psychological processes and motives (e.g., values, beliefs, and self-concept) are changing over time in American society to produce these changes in behavior. Importantly, cooperation in social dilemmas, including the studies reported in the CoDa (Spadaro et al, in press), can be used to test many other theories about cooperation and prosocial behavior that are not addressed in the present work, such as understanding prosocial personality (Thielmann et al, 2020), how institutional rules affect cooperation (Jin et al, 2021), how cooperation varies across regions, countries, and cultures around the world (Spadaro, Graf, et al, 2022). The annotation of these studies has been made open access for researchers to use to test hypotheses and answer research questions about cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a recent meta-analysis found that people in higher relational mobility societies did not contribute more in incentivised social dilemma experiments (Spadaro et al, 2022). However, this previous work has focused on only a subset of possible measures of prosocial behaviours and attitudes: social support and cooperation in social dilemmas.…”
Section: Partner Choice Does Not Predict Prosociality Across Countriesmentioning
confidence: 95%
“…For example, research has shown that people in higher relational mobility societies provide social support to others more frequently (Kito et al, 2017), have greater trust in strangers (Thomson et al, 2018) and are more likely to give gifts in romantic relationships (Komiya et al, 2019). Conversely, a recent meta-analysis found that people in higher relational mobility societies did not contribute more in incentivised social dilemma experiments (Spadaro et al, 2022). However, this previous work has focused on only a subset of possible measures of prosocial behaviours and attitudes: social support and cooperation in social dilemmas.…”
mentioning
confidence: 99%